Literature Review: Pengaruh Senam Kaki Diabetes terhadap Kadar Glukosa Darah pada Klien Diabetes Melitus - Siti Amiroh Khoirunnisa; Wiwiek Natalya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Diabetes is characterized by blood sugar exceeding normal levels (hyperglycemia). Diabetes mellitus is a chronic disease that cannot be cured. However, blood glucose levels can be controlled using the five pillars of diabetes mellitus management. One of them is by doing physical exercise. A recommended physical exercise for clients with diabetes mellitus without ulcers is to do diabetic foot exercises. Purpose: To determine the effect before and after diabetic foot exercise on blood glucose levels in clients with diabetes mellitus through a literature review. Methods: The data collection technique used a literature review of five articles from online databases on GoogleScholar and Pubmed published in 2016-2020. The critical analysis instrument used is Hawker. Results: the results of the literature review of the five articles showed that from 171 respondents, three research articles were using the T-test method. It can be concluded that there is an effect of diabetic foot exercise on blood glucose levels in clients with diabetes mellitus with p < 0.005. Meanwhile, two articles use the Wilcoxon method. One article concluded that there is an effect of diabetic foot exercise on blood glucose levels. Another article concluded that there is no effect of diabetic foot exercise on blood glucose levels in clients with diabetes mellitus with p> 0.005. Conclusion: there is an effect of diabetic foot exercise on blood glucose levels in patients with diabetes mellitus.